An Analytical Solution to Heat Equation - Ion Riza; Marius Constantin Popescu (Journal of Basic & Applied Sciences, 2014)
The present paper explores theoretical aspects of solving the heat equation in the monodimensional case. The proposed study method is the variables separation method, finding thus an original solution, which is compared with the numerical solution obtained by finite difference method.